Interleukin-8 is associated with acute and persistent dysfunction after optic neuritis. (December 2014) - Rossi, S; Motta, C; Studer, V; Rocchi, C; Macchiarulo, G; Barbieri, F; Marfia, GA; Furlan, R; Martino, G; Mancino, R; Centonze, D
Background: Acute optic neuritis is often in association with multiple sclerosis (MS). Proinflammatory cytokines trigger neuronal damage in neuroinflammatory disorders but their role in optic neuritis is poorly investigated. Objective: The objective of this work is to investigate the associations of intrathecal contents of proinflammatory cytokines with transient and persistent dysfunctions after optic neuritis. Methods: In 50 MS patients followed for up to six months, cerebrospinal fluid (CSF) levels of IL-1β, TNF and IL-8 were determined, along with clinical, neurophysiological and morphological measures of optic neuritis severity. Results: Visual impairment, measured by high- and low-contrast visual acuity, and delayed visual-evoked potential (VEP) latencies were significantly correlated to IL-8 levels during optic neuritis. IL-8 at the time of optic neuritis was also associated with persistent demyelination and final axonal loss, inferred by VEP and optical coherence tomography measures, respectively. Contents of IL-8 were correlated to functional visual outcomes, being higher among patients with incomplete recovery. Multivariate analysis confirmed that IL-8 significantly predicted final visual acuity, at equal values of demographics and baseline visual scores. Conclusion: Our study points to IL-8 as the main inflammatory cytokine associated with demyelination and secondary neurodegeneration in the optic nerve after optic neuritis.